300 million years of diversification: elucidating the patterns of orthopteran evolution based on comprehensive taxon and gene sampling. (9th March 2015) - Song, Hojun; Amédégnato, Christiane; Cigliano, Maria Marta; Desutter‐Grandcolas, Laure; Heads, Sam W.; Huang, Yuan; Otte, Daniel; Whiting, Michael F.
Abstract: Orthoptera is the most diverse order among the polyneopteran groups and includes familiar insects, such as grasshoppers, crickets, katydids, and their kin. Due to a long history of conflicting classification schemes based on different interpretations of morphological characters, the phylogenetic relationships within Orthoptera are poorly understood and its higher classification has remained unstable. In this study, we establish a robust phylogeny of Orthoptera including 36 of 40 families representing all 15 currently recognized superfamilies and based on complete mitochondrial genomes and four nuclear loci, in order to test previous phylogenetic hypotheses and to provide a framework for a natural classification and a reference for studying the pattern of divergence and diversification. We find strong support for monophyletic suborders (Ensifera and Caelifera) as well as major superfamilies. Our results corroborate most of the higher‐level relationships previously proposed for Caelifera, but suggest some novel relationships for Ensifera. Using fossil calibrations, we provide divergence time estimates for major orthopteran lineages and show that the current diversity has been shaped by dynamic shifts of diversification rates at different geological times across different lineages. We also show that mitochondrial tRNA gene orders have been relatively stable throughout the evolutionary history of Orthoptera, but a major tRNA gene rearrangement occurred in the common ancestor of Tetrigoidea and Acridomorpha, thereby representing a robust molecular synapomorphy, which has persisted for 250 Myr.